Undressing Rizal’s Message: Clothing and Gender in Noli me tángere - Coo, Stephanie; Ateneo (Archīum Ateneo, 2020)
Thisarticle explores José Rizal’s Noli me tángere as a site and source of rumination on clothing’s historical significance in the Philippines in the late nineteenth century. The characters in the novel represented various social types, whose clothes contribute to our knowledge of nineteenth-century men’s and women’s clothing and to the role clothes played in colonial power relationships, status competition among natives, and gender politics. Clothes suggested a period of ferment when colonial divides were being blurred in part by intermarriages and upward social mobility. Through clothing, the novel also showed how female body parts were sexualized and subjected to the male gaze.KEYWORDS: PHILIPPINE CLOTHING • SPANISH COLONIALISM • CLOTHING AND GENDER • JOSÉ RIZAL • NOLI ME TÁNGERE